Energy transitions: the case of South African electric security - Van Der Merwe, Melani (Department of Public Law, 2018)
Modern civilizations have evolved to be highly dependent on electrical energy. The exponentially growing renewables market has signaled transitions in electricity sectors that have traditionally been dominated by fossil fuel electricity. Various theoretical debates have recently emerged surrounding the processes of socio-technical transition, focusing on the pathways of transition, the levers for radical change and path-dependencies within these systems. The Multi-Level Perspective on Socio-technical Transitions is one such theory. This perspective views socio-technical change as a factor of interdependent shifts between three analytical levels observed within the system: the socio-technical regime, the socio-technical niche and the landscape. In accordance with this theory, radical change is generally observed as originating at niche level. Irregularities within the dominant regime and landscape pressures allow for niche innovations to break through into the dominant regime in processes of socio-technical transition. Toward understanding actor influences on energy transitions, considerable attention has been paid to actor's impact on governance processes through: patterns of consumption, the shaping of legislation and technical innovations, by socio-technical transitions theories. However less attention has been paid to the ways in which actors in renewable electricity markets are: forming networks toward the establishment of new regimes and governing processes at niche level, and consequently how actor governance has impacted the established perceptions and available pathways for realizing electric security. This thesis, builds on the Multi-Level Perspective, through an exploration of how actors govern socio-technical systems at niche level, paying careful attention to the modalities of power giving and power taking that allow for the development of networks of people and things toward the stabilization of novel socio-technical practices, innovations and developmental trajectories. It does this through a networked analysis of how different actors with different interests cooperate to open up innovative social and technological pathways.